Can One Cook Spoil the Broth? The Effects of Minimum Pacing Style in Student Chef Teams (Journal of Organizational Psychology, 2021)
Can an entire team be held back by one team member with the lowest pacing style? This question has been unexplored because most team composition research focuses on average levels within a team and because pacing style is a relative newcomer to the temporal individual difference literature. We examined the effects of teams’ minimum pacing style (how effort is allocated over time to meet deadlines) member in student chef teams. Members with the lowest pacing style acted as weak links in their teams, reducing both team creativity and timeliness. Study findings show promise for continued investigation of the compositional effects of minimum pacing style on team outcomes and temporal leadership (leader behaviors that coordinate the pace of task accomplishment in teams) as an intervention to attenuate the negative effects of the weakest link member.
Keywords: organizational psychology; pacing styles, teams, temporal leadership, creativity, timeliness, conjunctive tasks